Medical devices regulatory aspects: a special focus on polymeric material based devices - Sridhar, Radhakrishnan; Pliszka, Damian; Luo, He-Kuan; Chin Lim, Keith H.; Ramakrishna, Seeram (Current Pharmaceutical Design, 2015)
Medical devices form a broad range of appliances from a basic nanoparticle coating or surgical gloves to a complicated laser therapy device. These devices are designed to support patients, surgeons and healthcare personnel in meeting patients’ healthcare needs. Regulatory authorities of each country regulate the process of approval, manufacturing and sales of these medical devices so as to ensure safety and quality to patients or users. Recent recalls of medical devices has increased importance of safety, awareness and regulation of the devices. Singapore and India have strong presence and national priorities in medical devices development and use. Herein we capture the rationale of each of these national regulatory bodies and compare them with the medical devices regulatory practices of USA and European nations. Apart from the comparison of various regulatory aspects, this review will specifically throw light on the polymer material based medical devices and their safety.
Keywords: active pharmaceutical ingredients